Editorial: diabetes in HIV‐infected patients—do not blame the usual suspect! Authors' reply. Issue 4 (24th July 2018) - Provoost, A.; Dramé, M.; Bani‐Sadr, F.
Abstract : Linked Content This article is linked to Provoost et al and Höner zu Siederdissen and Mederacke papers. To view these articles visithttps://doi.org/10.1111/apt.14812 andhttps://doi.org/10.1111/apt.14863 .